Settlement of Problematic Financing in Sharia Banks from the Perspective of Sharia Economic Law: A Case Study of Bank BTN Syariah in Surabaya - Rachman, Mudhoffar; Rosyad, Ubaidillah; Sabila, Nita (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Islamic housing financing is one of the main products of Islamic banking, yet it involves relatively high risk, particularly in the property sector. Bank BTN Syariah, as a Sharia Business Unit (UUS), focuses heavily on housing financing through Sharia Home Ownership Loan (KPR Syariah) products, making it vulnerable to customer default. This study aims to analyze the mechanism for resolving problematic financing at Bank BTN Syariah Surabaya and to examine its conformity with the principles of sharia economic law. The research employs an empirical juridical method with a qualitative approach. Data were obtained through interviews with Bank BTN Syariah Surabaya and documentation studies, supported by primary and secondary legal materials, including statutory regulations and fatwas of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI). Data analysis was conducted descriptively by linking practical settlement mechanisms with applicable Sharia economic law principles. The findings show that problematic financing is resolved through restructuring, customer deliberation, and, as a last resort, the sale of collateral. These mechanisms generally align with the values of Sharia economic law, particularly the principles of justice, benefit (maslahah), and protection of the parties. However, improving customers' legal literacy and understanding of Sharia contracts remains necessary to minimize problematic financing in the future.